Effect of Adhesive-Particle Ratio and Avocado Seed Filler on the Characteristics of Particleboard Made from Oil Palm Empty Fruit Bunches - Mirna Rahmah Lubis; Fachrul Razi; Tasha Salsabilla; Kausar Kausar; Fezi Rizky Husein (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Conservation efforts in Indonesian forests have become a development priority crucial for maintaining ecosystem balance, coupled with the endeavor to preserve the judicious use of wood. The demand for wood increases with its development, but its diminishing availability poses challenges for the industry. Efforts to reduce this impact involve finding environmentally friendly solutions, namely by utilizing waste to create new products. Therefore, this study focuses on reprocessing oil palm fruit bunches into particleboard using polyvinyl acetate and dibutyl phthalate as adhesives. The variables studied include the adhesive/particle ratio and the percentage of avocado seed filler. The resulting composite was tested for modulus of rupture, moisture content, modulus of elasticity, thickness swelling, density, and tensile strength. These results show that particleboard with an adhesive/particle ratio of 1.6 and 2% avocado seeds can enhance modulus of rupture, thickness swelling, moisture content, and density under the SNI 03- 2105-2006 standard.